Synthesis, Characterization and Photocatalytic Performance of Poly-3-Thenoic Acid/Cu-TiO2 Nanohybrid for Efficient Visible Light Assisted Degradation of Bismarck Brown R - Raju, Imandi Manga; Rao, Tirukkovalluri Siva; Rao, Miditana Sankara (Trends in Sciences, 2022)
The present work reported on the synthesis and characterization of Poly-3-Thenoic acid/Cu-TiO2 nanohybrid (PCuT) for the photocatalytic degradation of organic azo dye pollutant from wastewater. The as-synthesized nanohybrid by an in-situ modified sol-gel method including chemical oxidative polymerization was characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, UV-visible diffuse reflectance spectroscopy (UV-vis.DRS), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM) and Brunauer-Emmet-Teller (BET) surface area analysis. The characterization results revealed the formation of small aggregates of polymer contained high crystalline anatase TiO2 nanoparticles (XRD) with narrowed bandgap energy (UV-vis.DRS), decreased particle size (TEM) with smooth surface morphology (SEM) and large surface area (BET). All the constituent elements of the polymer and Cu-TiO2 were found in the PCuT nanohybrid material (EDX) and their chemical interaction studied by FT-IR confirmed the stability of the nanohybrid. The photocatalytic activity of the nanohybrid was tested by the degradation of Bismarck Brown R dye under visible light irradiation. To enhance the photocatalytic efficiency, effects of various catalyst/dye reaction parameters such as polymer content, solution pH, catalyst dosage, and initial dye concentration were studied and optimized. HIGHLIGHTS Poly-3-Thenoic acid/Cu-TiO2 nanohybrid material was successfully synthesized by in situ modified sol-gel process Poly-3-Thenoic acid has enhanced the visible light absorption capacity of anatase TiO2 in nanohybrids Electron-hole recombination in TiO2 was effectively inhibited by Cu doping Bismark Brown R, an organic pollutant was successfully degraded in 75 min of visible light irradiation GRAPHICAL ABSTRACT